Law, NFTs, and Pop Culture: Analyzing Intellectual Property in Indonesia through the Lens of Modern Cultural Products - Tobing, Joel Jordan; Situmeang, Ampuan; Disemadi, Hari Sutra (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
The development of technology and digital transformation has led to the growth of industries such as the creative business industry. One of its impacts is the emergence of Non-Fungible Tokens (NFTs). NFTs are digital assets in the form of tokens representing ownership of a digital artwork. In Indonesia, NFTs currently lack specific legislative regulations, and there is no explicit and clear regulatory framework regarding the protection of NFTs in terms of their intellectual property aspects. Therefore, this study examines the development of NFTs in Indonesia, along with the legal position and protection of NFTs based on intellectual property law in Indonesia. In this research, the author employs a normative juridical research method with a legislative approach. Based on the research findings, it is evident that the development of NFTs, both globally and nationally, is quite significant. The public is increasingly becoming acquainted with NFTs, which have substantial prospects and are associated with many high-commercial-value works. Regarding NFTs as creative works, the regulation that accommodates the protection of intellectual property for NFTs in Indonesia is Law No. 28/2014. It is known that NFTs can take the form of images, paintings, videos, and music, which are considered parts of creations protected by copyright.